Circulating Mitochondrial DNA Stimulates Innate Immune Signaling Pathways to Mediate Acute Kidney Injury - Liu, Jiaye; Jia, Zhanjun; Gong, Wei (Frontiers in Immunology, 2021)
Mitochondrial dysfunction is increasingly considered as a critical contributor to the occurrence and progression of acute kidney injury (AKI). However, the mechanisms by which damaged mitochondria mediate AKI progression are multifactorial and complicated. Mitochondrial DNA (mtDNA) released from damaged mitochondria could serve as a danger-associated molecular pattern (DAMP) and activate the innate immune system through STING, TLR9, NLRP3 and some other adaptors, and further mediate tubular cell inflammation and apoptosis. Accumulating evidence has demonstrated the important role of circulating mtDNA and its related pathways in the progression of AKI, and regulating the proteins involved in these pathways may be an effective strategy to reduce renal tubular injury and alleviate AKI. Here, we aim to provide a comprehensive overview of recent studies on mtDNA-mediated renal pathological events to provide new insights in the setting of AKI.